2021
DOI: 10.3897/neobiota.70.65454
|View full text |Cite
|
Sign up to set email alerts
|

Invasive predators induce plastic and adaptive responses during embryo development in a threatened frog

Abstract: Invasive predators can strongly affect native populations. If alien predator pressure is strong enough, it can induce anti-predator responses, including phenotypic plasticity of exposed individuals and local adaptations of impacted populations. Furthermore, maternal investment is an additional pathway that could provide resources and improve performance in the presence of alien predators. We investigated the potential responses to an alien predator crayfish (Procambarus clarkii) in a threatened frog (Rana lata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 64 publications
5
10
0
Order By: Relevance
“…Studies examining predator effects on the developmental rates of both eggs and larvae are rare because few predators consume both eggs and larvae simultaneously. Muraro et al (2021) used a stage-nonspecific predator (Procambarus clarkii) and found, in concordance with our results, a reduction in hatching time in Rana latastei embryos. However, they did not study larval development.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Studies examining predator effects on the developmental rates of both eggs and larvae are rare because few predators consume both eggs and larvae simultaneously. Muraro et al (2021) used a stage-nonspecific predator (Procambarus clarkii) and found, in concordance with our results, a reduction in hatching time in Rana latastei embryos. However, they did not study larval development.…”
Section: Resultssupporting
confidence: 90%
“…Finding a general tendency in the phenotypic plasticity responses of prey across a broad range of animal predators (different taxa and feeding spectra), environmental and experimental conditions is a challenge even in anurans themselves (Relyea et al 2018). However, in frogs, the earlier hatching time was generally associated with smaller size at hatching (Capellán and Nicieza 2007;Chivers et al 2001;Ireland et al 2007;Laurila et al 2002) and lower developmental stage (Capellán and Nicieza 2007;Chivers et al 2001;Ireland et al 2007;Laurila et al 2002;Muraro 2021), and our results confirm this relationship. In some cases, earlier hatched tadpoles performed higher growth rate and reached the size of later hatched tadpoles at metamorphosis (Capellán and Nicieza 2007).…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Muraro et al (2021) used a stage-nonspecific predator (Procambarus clarkii) and found, in concordance with our results, a reduction in hatching time in Rana latastei embryos. However, they did not study larval development Ireland et al (2007).…”
supporting
confidence: 90%
“…Native and naive prey may fail to detect the novel predator adequately as a dangerous threat, resulting in no (Cox and Lima 2006;Sih et al 2010) or inefficient antipredator responses to counter the predator's attack strategies (Sih et al 2010;Strauss et al 2006). However, when responses in hatching time in naive prey are detected, they are often explained by the presence of syntopic, taxonomically related predators (Melotto et al 2021;Muraro et al 2021;Sih et al 2010), although the time since invasion may also play an important role (Gomez-Mestre and Díaz-Paniagua 2011; Nunes et al 2013). Our results suggested that a common evolutionary history is not necessary for a detectable response.…”
Section: Discussionmentioning
confidence: 70%